The Impact Of Sales Strategies Using The NUP Model On The Performance Of Property Agents (A Case Study In Surabaya, Sidoarjo And Gresik) - Indra Purnama; Denpharanto Agung Krisprimandoyo; Rismawati Sitepu (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study investigates the effectiveness of the NUP (Ordering Number) sales method used by property developers to market housing units before official launch or project completion. While some developers report strong sales outcomes using this model, others fall short of targets. The research aims to examine whether compensation, training, experience, product knowledge, and competitive advantage influence the sales performance of property agents involved in NUP-based sales. A quantitative approach was employed, involving 123 property agents from Surabaya, Sidoarjo, and Gresik, selected through purposive sampling based on criteria such as experience with NUP sales, product knowledge training, and tenure in the property sector. Data collection was conducted via online questionnaires during March–April 2025, and analysis was performed using Multiple Linear Regression with SPSS 25.0. Results show that, simultaneously, all five variables—compensation, training, experience, product knowledge, and competitive advantage affect sales performance. However, in partial testing, only compensation, training, and experience have a significant positive impact, while product knowledge and competitive advantage do not. The coefficient of determination (R²) indicates that 27% of the variance in sales performance is explained by the five tested variables, leaving 73% attributed to other factors not covered in this study.